GAMIFIKASI PEMBELAJARAN DENGAN MENGGUNAKAN KAHOOT PADA MATA KULIAH PPKn MI/SD - Maulana Arafat Lubis; Nisha Marina; Marhamah Marhamah; Nashran Azizan (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2021)
AbstractThe trend of gamification is currently increasingly popular in the field of education. Gamification such as Kahoot is increasingly being used in learning environments to increase students' interest, motivation, and learning outcomes. This study aims to see the effectiveness of Kahoot in learning in MI/SD PPKn courses. This research is quantitative by using the survey research method. Students of the PGMI IAIN Padangsidimpuan Study Program as the population in this study. The sampling technique used in this study is probability sampling with the type of simple random sampling. The sample was determined using the calculator.net platform. The sample was 104 respondents from 729 populations. A Google Form-assisted questionnaire was used as a data collection technique in this study. STATCAL software is used as a machine to analyze the data of this research. The study results explained that, on average, the survey who responded agreed there were 64 (61.17%) students, while those who responded strongly agreed there were 32 (30.33%) students. So, the Kahoot application as learning gamification in MI/SD PPKn courses at the PGMI IAIN Padangsidimpuan Study Program looks effective. Keywords: Gamification of learning, Kahoot, PPKn MI/SD AbstrakTren gamifikasi saat ini semakin populer di bidang pendidikan. Gamifikasi seperti Kahoot semakin banyak digunakan di lingkungan belajar sebagai cara untuk meningkatkan minat, motivasi, dan hasil belajar peserta didik. Penelitian ini bertujuan untuk melihat keefektifan Kahoot dalam pembelajaran pada mata kuliah PPKn MI/SD. Riset ini berjenis kuantitatif dengan menggunakan metode penelitian survey. Mahasiswa Prodi PGMI IAIN Padangsidimpuan sebagai populasi dalam penelitian ini. Teknik sampel yang digunakan probability sampling dengan jenis sampel random sampling. Sampel ditentukan berbantuan platform calculator.net, sampelnya ialah 104 responden dari 729 populasi. Kuesioner berbantuan Google Form dijadikan sebagai teknik pengumpulan data dalam penelitian ini. Software STATCAL dijadikan sebagai mesin untuk menganalisis data penelitian ini. Hasil penelitian memaparkan bahwa rata-rata survey yang merespon setuju ada 64 (61,17%) mahasiswa, sedangkan yang merespon sangat setuju ada 32 (30,33%) mahasiswa. Jadi, aplikasi Kahoot sebagai gamifikasi pembelajaran dalam mata kuliah PPKn MI/SD di Prodi PGMI IAIN Padangsidimpuan terlihat efektif. Kata kunci: Gamifikasi pembelajaran, Kahoot, PPKn MI/SD